Student Perspectives on the English Camp Parade Season 5 at Universitas Bhinneka PGRI - Densi Himelda Yusvita Dewi; Dina Kartikawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to explore the perspectives of sixth-semester students regarding the implementation of the English Camp Parade (ECP) Season 5 at Universitas Bhinneka PGRI. ECP is an activity-based learning program designed to promote contextual English use through interactive activities such as drama performances, quizzes, and group discussions. Using a qualitative approach, the study involved 14 purposively selected sixth-semester students and 2 key informants (the ECP coordinator and the chairperson of the English Student Association). Data were collected through semi-structured interviews, open-ended questionnaires, and observation, and analyzed thematically. The findings indicate that most students responded positively to the program, particularly in terms of increased speaking confidence, vocabulary development, and cross-semester collaboration. However, some students perceived the activities as more entertaining than academically structured. These results highlight the need to improve the program design by balancing educational content with engaging activities. The study contributes to the development of activity-based English learning strategies in higher education contexts.